Health-related quality of life among radiology technicians in Turkish hospitals: a cross sectional study - AKYURT, NURAN (Springer Science and Business Media Deutschland GmbH, 2021)
Background: Health related quality of life (HRQoL), despite its potential bi-directional interaction with occupational risks, has not been extensively addressed among radiology technicians. Objective: To evaluate HRQoL among radiology technicians in relation to sociodemographic and occupational factors. Methods: A total of 115 radiology technicians who were employed in three big hospitals located in Istanbul province were included on a voluntary basis in this cross sectional questionnaire-based study conducted between June 2019 and August 2019. The questionnaire form elicited items on socio-demographic characteristics, occupational characteristics and the 36-item Short-form Health Survey (SF-36), respectively. Results: Overall, 94.8% of technicians confirmed previous training on radiation protection and safety, while 92.2% noted distrust in their knowledge on radiation protection and patient dosage. In addition, 47.8% of technicians noted seldom use of radiation protection measures and 55.7% noted distrust in reliability of radiation exposure measurements. The multiple regression analysis revealed that older age, female gender, working at a university hospital and seldom use of protection significantly predicted poor HRQoL (p = 0.042 to 0.001), while working in interventional radiology and having trust in radiation exposure measurements predicted better HRQoL (p = 0.006 to 0.001) in terms of certain domains. Conclusion: In conclusion, our findings revealed lack of trust in current self-knowledge on radiation protection and safety by majority of radiology technicians and seldom use of radiation protection measures by half of them, despite previously trained on radiation protection and safety. Certain occupational factors and factors related to radiation protection and safety were also amongst the significant determinants of poor HRQoL. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Cross sectional studies; Knowledge; Quality of life; Radiation protection; Radiation safety; Radiology technicians; SF-36; Turkey